EDUCATIONAL LAWS AND POLICIES IN NIGERIA: THEIR IMPACT ON NATIONAL DEVELOPMENT, CHALLENGES, AND STRATEGIES FOR EFFECTIVE IMPLEMENTATION - Berebon, Charles (Universitas Negeri Makassar, 2024)
Education is a fundamental human right and a catalyst for social justice and national development. It empowers individuals, fosters societal progress, and drives economic, political, and human advancement. In Nigeria, education is envisioned as a tool for transforming individuals into responsible citizens, as outlined in the National Policy on Education (2014). This policy emphasizes equal access to functional education for all, regardless of background or socioeconomic status, aligning with the nation's goal of building an inclusive and productive society. However, despite the strong emphasis on education policies, implementation challenges have hindered their transformative potential, affecting academic excellence and social progress. This paper explores the historical development and philosophical foundations of educational laws and policies in Nigeria, analyzing the sociopolitical and cultural complexities that affect their adaptation and effectiveness. It offers insights into addressing these challenges to ensure educational reforms contribute meaningfully to national development